Information or Evidence? Abandoning Imaginary Worlds for Blockchains in Health Technology Assessment - Paul Langley (University of Minnesota Libraries Publishing, 2018)
Commentaries published in INNOVATIONS in Pharmacy over the past 2 years have made the case that, as a basis for formulary decision making, the construction of imaginary modeled worlds fails to meet the standards of normal science. As such, they should be rejected as a basis for decision-making. While their proponents argue that imaginary constructs are key sources of information for formulary decisions, the fact is that the claims made from those models are impossible to validate. Indeed, they were never intended to be validated. Claims for product performance should be presented in evidentiary terms. That is, they should be credible, evaluable and replicable. If the commitment to imaginary worlds in technology assessment is to be abandoned a key requirement is for platforms that allow claims to be assessed in real time and in a timeframe that is meaningful to decision makers. Recent developments in blockchain technology offer the prospects for platforms that meet criteria for claims assessment.   Article Type: Commentary